Transformasi Gerakan Sosial Lingkungan di Media Sosial: Analisis Bibliometrik - Fajar Alan Syahrier (Prodi Sosiologi Universitas Mataram, 2026)
The digital era has transformed environmental social movements by reshaping how environmental awareness is fostered, collective action is mobilized, and environmental issues are advocated through social media platforms. This study aims to analyze the development of scientific literature on the transformation of environmental social movements in social media using a bibliometric approach. The dataset consists of 298 Scopus-indexed articles published between 2015 and 2025, selected following the PRISMA 2020 guidelines. The data were analyzed using the Bibliometrix package through Biblioshiny in R to identify publication trends, the most relevant sources and authors, and the thematic structure of the field. The findings reveal a growing number of publications, indicating increasing scholarly interest in the relationship between social movements, social media, and environmental issues. Co-occurrence analysis shows that the literature is centered on the interconnected themes of social movement, social media, and climate change, supported by topics such as sustainability, environmental justice, citizenship, environmental policy, and collective action. The study demonstrates that the transformation of environmental social movements is reflected in the shift of issues toward climate change and sustainability, the emergence of digital network-based mobilization mechanisms, and the growing orientation of movements toward policy advocacy and environmental governance. These findings highlight the role of social media as a crucial infrastructure for collective identity formation, digital resource mobilization, and broader public participation in contemporary environmental social movements.